DECISION MAKING IN REVERSE LOGISTICS PROCESSES USING SIMULATION - Gulsun, Bahadir; Tuzkaya, Gulfem; Bekil, Turgut (YILDIZ TECHNICAL UNIV, 2008)
Parallel with the increasing environmental problems, the attention to reverse logistics is increasing both in the academic and the industrial research area. Various decision making techniques are utilizes related with the reverse logistics, however, the simulation is utilized very rare. In this research, a simulation model for a reusable container system is built via a commercial software ARENA 9.0.. After giving the detailed description of the model structure; through this model, different network alternatives, dispatching rules and vehicle allocation schemes are compared. Here the aim is to find the best combination which will provide superior customer satisfaction according to some performance measures such as turnover time and waiting time for packaging dispatch. In conclusion, the simulation results which show that different combinations of these policies affect the customer satisfaction levels differently are discussed.
Keywords: Reverse logistics; returnable containers; simulation; Engineering